Socio-economic and labor conditions of students and alumni of a higher education institution in the periurban area of the metropolitan valley of Mexico city: an exploratory study - Mejía Pérez, Gustavo; Espinoza Ortega, Óscar (Universidade Estadual de Campinas, 2017)
The paper presents the analysis of the labor and economic situations of alumni from a higher education institution located in the Metropolitan Area of Mexico City. The study anazlyed data provided by the Institutional Alumni Tracking System of the Autonomous University of the State of Mexico from 2000 to 2013. The results of the analysis shows entries into the labor market differentiated by gender and degree, which possibly determine different itineraries in the students’ and alumni’s processes of family independence.